2013
DOI: 10.3168/jds.2012-5887
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of processing companies for attributes of Swiss milk: A conjoint analysis in a business-to-business market

Abstract: This study aimed to determine key attributes of milk that drive a processor's supply decisions and possibilities for differentiation based on these product attributes. Feedback-driven exploration was applied to derive product attributes relevant to the buying decision. Conjoint analysis with hierarchical Bayes estimation methods was used to determine the relative importance of attributes. Results show that the technical aspects of milk, as well as the price and country of origin, dominate the buying decision. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Using conjoint analysis, Bai et al (2007) identified attributes such as low fat content, HTST pasteurization, and natural taste as drivers of liking for fluid milk. In a study by Boesch (2013), Swiss milk consumers preferred milk that was GMO free (a particular concern) and of local origin. More recently, McCarthy et al (2017b) used a conjoint analysis survey with 702 dairy consumers followed by individual interviews with 172 consumers to probe consumer key drivers for purchase, beliefs, and values for milk compared with plant-based beverages.…”
Section: Consumer-focused Sensory Tests: Affective Sensory Testsmentioning
confidence: 99%
“…Using conjoint analysis, Bai et al (2007) identified attributes such as low fat content, HTST pasteurization, and natural taste as drivers of liking for fluid milk. In a study by Boesch (2013), Swiss milk consumers preferred milk that was GMO free (a particular concern) and of local origin. More recently, McCarthy et al (2017b) used a conjoint analysis survey with 702 dairy consumers followed by individual interviews with 172 consumers to probe consumer key drivers for purchase, beliefs, and values for milk compared with plant-based beverages.…”
Section: Consumer-focused Sensory Tests: Affective Sensory Testsmentioning
confidence: 99%
“…The method has been applied successfully for tackling several marketing decisions such as optimal design of new products, target market selection, pricing a new product, and competitive reactions. In market analysis CA is applied to identify which attributes of a product or service are most important to consumers thus it is an important tool in the evaluation of the preferences assigned by the consumer to the various attributes that comprise a good (SPSS, 1997, p.1;Henson & Cranfield, 2009, p.258;Boesch, 2013Boesch, , p.2183Hailu Boecker, Rao, 2014, p.1;Barnebeu & Diaz, 2016, p.2). The basis of this approach is based on the fact that consumers' benefit maximization is derived from the properties of the products.…”
Section: Methodsmentioning
confidence: 99%
“…Salah satu upaya meningkatkan penjualan yaitu dengan menjual produk yang sesuai permintaan dan preferensi konsumen, hal ini dapat meningkatkan penjualan dan produk lebih cepat terjual. Perusahaan yang memiliki orientasi pasar yang tepat dan memanfaatkan keunggulan posisi dapat mencapai kinerja yang unggul dibandingkan dengan pesaing mereka (Boesch, 2013).…”
Section: Pengaruh Atribut Susu Pasteurisasi Rumah Susu Kud Argopuro T...unclassified